MODELLING AND FORECASTING VOLATILITY BY GARCH-TYPE MODELS: THE CASE OF VIETNAM STOCK EXCHANGE - Mai, Thi Thanh Hien (2008)
A number of previous studies have been devoted to investigate properties of volatility in emerging markets. In attempt to contribute to literature, this dissertation examines stock return volatility in Vietnam stock market. The empirical investigation is conducted by means of alternative GARCH models including both symmetric and asymmetric models with a data set of VN-Index over six years period from March, 2002 to March, 2008. The findings present the inappropriateness of asymmetric GARCH in modelling Vietnam stock return volatility. The results also provide evidence of the superiority of GARCH (1,1) and GARCH (2,1) over the other GARCH models. However, the excess kurtosis and skewness in residual series of Vietnam stock return are still reveal even with the best-performing GARCH models. Moreover, we detect the risk-reward relation in the Vietnam stock market by GARCH-M model. Regarding the forecasting capability, the results favour the GARCH (1,1) and GARCH (2,1). The findings are evidenced by three different measures used to evaluate the forecasting accuracy, though these statistics fail to present the clear distinction between the best models in forecasting.